The application of postactivation potentiation methods to improve sprint speed - Healy, R.; Comyns, T. M. (Strength and Conditioning Journal, 2017)
This article examines the application of a variety of modalities to elicit a postactivation potentiation (pap) response in sprinting. We present the existing literature on the acute effects of back squats, power cleans, plyometrics, and sled pulling on sprint distances ranging from 5 to 50 m. We also discuss and provide an example of how coaches can assess the individual effects of pap protocols on their athletes to identify whether a protocol elicits an acute improvement or impairment in performance. Finally, we provide practical recommendations on how coaches can incorporate these methods into a sprint training session.